Association between adverse pregnancy outcome and imbalance in angiogenic regulators and oxidative stress biomarkers in gestational hypertension and preeclampsia - Turpin, C.A.; Sakyi, S.A.; Owiredu, W.K.B.A.; Ephraim, R.K.D.; Anto, E.O. (BioMed Central Ltd., 2015)
Background: Gestational hypertension (GH) and Preeclampsia, (PE) are the most complicated amongst hypertensive disorders of pregnancy. The mechanism that links hypertension in pregnancy to adverse maternal outcomes is not fully understood though some relate this to endothelial dysfunction originating from an imbalanced angiogenic regulators and oxidative stress biomarkers. This study assessed the correlation between angiogenic regulators and oxidative stress biomarker levels with adverse pregnancy outcomes among GH and PE participants. Methods: A cohort of pregnant women who received antenatal care at the Obstetrics and Gynaecology department of the Komfo Anokye Teaching Hospital (KATH) were followed. During their antenatal visits, 100 developed PE and 70 developed GE, of these, 50 PE and 50 GH gave informed consent. Their blood samples were taken at time of diagnosis and 48 h post-partum. 50 other aged-matched women who did not develop neither GH nor PE were selected as controls. Placental growth factor (PLGF), soluble fms-like tyrosine kinase 1 (sFlt-1) and 8-epi-prostaglandin F2alpha (8-epi-PGF2aα) levels were estimated by ELISA and total antioxidant capacity (T-AOC) was measured spectrophotometrically. Graphpad Prism was used for data analysis. Results: Median levels of sFlt-1, 8-epi-PGF2aα and sFlt-1/PLGF were elevated among participants with PE co-existing with intrauterine fetal death (IUFD), placental abruptio, placental previa, HELLP syndrome and intrauterine growth restriction (IUGR) compared to PE without adverse outcomes (p = 0.041, p = 0.005, p = 0.0002). Levels of PLGF, T-AOC and PLGF/sFlt-1 were significantly reduced among participants with PE co-existing with IUFD, placental abruptio, placental previa, HELLP syndrome and IUGR compared to PE without adverse outcomes (p = 0.0013, p = 0.006, p < 0.0001). A significant negative correlation of IUGR (p = 0.0030; p < 0.0001), placental abruptio (p < 0.0001; p < 0.0001), IUFD (p < 0.0001; p < 0.0001), stillbirth (p = 0.0183 and p < 0.000), and postpartum haemorrhage (PPH) (p = 0.0420; p = 0.0044) were associated with both PLGF and T-AOC whilst a significant positive correlation of IUGR, placental abruptio (p < 0.0001; p < 0.0001), IUFD (p < 0.0001; p < 0.0001), stillbirth (p < 0.0001; p < 0.0001), and PPH (p = 0.0043; p = 0.0039) were observed with both sFlt-1 and 8-epi-PGF2aα in PE. Conclusions: Imbalance in the levels of angiogenic regulators and oxidative stress biomarkers correlates with adverse pregnancy outcomes among PE participants. Early identification of these imbalance would alert health care givers in anticipation of adverse pregnancy outcome and thus increased surveillance during pregnancy and parturition and measures to ameliorate the adverse outcome.